Biomarkers of oxidative damage and antioxidant defense capacity in Caiman latirostris blood - Poletta, Gisela Laura (2016)
Several xenobiotics, and among them pesticides, can produce oxidative stress, providing a mechanistic basis for their observed toxicity. Chronic oxidative stress induces deleterious modifications to DNA, lipids and proteins that are used as effective biomarkers to study pollutant-mediated oxidative stress. No previous report existed on the application of oxidative damage and antioxidant defense biomarkers in Caiman latirostris blood, while few studies reported in other crocodilians were done in organs or muscles of dead animals. The aim of this study was to characterize a new set of oxidative stress biomarkers in C. latirostris blood, through the modification of conventional techniques: 1) damage to lipids by Thiobarbituric Acid Reactive Substances (TBARS), 2) damage to DNA by Comet assay modified with the enzymes FPG and Endo III, 3) antioxidant defenses: Catalase, Superoxide dismutase and Glutation; in order to apply them in future biomonitoring studies. We successfully adapted standard procedures for CAT, SOD, GSH and TBARS determination in C. latirostris blood. Calibration curves for FPG and Endo III showed that the three dilutions tested were appropriate to conduct the modified comet assay for detection of oxidized bases in C. latirostris erythrocytes. One hour of incubation allowed a complete repair of the damage generated. The incorporation of these biomarkers in biomonitoring studies of caiman populations exposed to xenobiotics is highly important considering that this species has recovered from a serious endangered state through the implementation of sustainable use programs in Argentina, and represents nowadays a relevant economic resource for many human communities.